English English: English - Alrizky R. Rachmansyah Putra (Jurnal Sentris, 2025)
Barcelona is today recognized as a major fashion capital, with many notable shopping districts playing host to some of the most notable and prestigious fashion brands in the world. The city has witnessed the start and rise of some of the most influential names in the industry and is ranked in the top 5 of the most important fashion capitals on earth. This status is thanks to the success of Barcelona and Catalonia’s cotton and textile industry from the 18th - 20th centuries, which allowed for the city’s fashion scene to flourish and become what it is today. However, it is impossible to talk about this success without mentioning the impact of trade relations between Catalonia and Colonial America. In this article, I wish to elaborate on the history of Catalonia’s textile industry and the impact that trade with Colonial America had on its evolution to allow the region to industrialize at a rapid pace and sustain a burgeoning fashion industry in Barcelona. Keywords: Barcelona fashion industry; Catalan textile industry; Colonial American trade